Respiratory, cardiovascular and metabolic effects of etorphine, with and without butorphanol, in white Rhinoceros (Ceratotherium Simum) - Meyer, Leith Carl Rodney (University of Pretoria, 2024)
Thesis (PhD (Paraclinical Sciences))--University of Pretoria, 2019.